2022
DOI: 10.1111/1541-4337.12958
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of wheat quality using near‐infrared spectroscopy: A comprehensive review

Abstract: Wheat is one of the most widely cultivated crops throughout the world. A great need exists for wheat quality assessment for breeding, processing, and products production purposes. Near‐infrared spectroscopy (NIRS) is a rapid, low‐cost, simple, and nondestructive assessment method. Many advanced studies associated with NIRS for wheat quality assessment have been published recently, either introducing new chemometrics or attempting new assessment parameters to improve model robustness and accuracy. This review p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…The applications of NIR spectroscopy in the quality and safety evaluation of tea products ( Lin and Sun, 2020 ), grain ( Caporaso et al, 2018 ), fruits and vegetables ( Nicolai et al, 2007 ), oilseeds and edible oils ( Li et al, 2020 ) have been reviewed. Although reviews on wheat-based products ( Badaró et al, 2022 ) and wheat flour ( Du et al, 2022 ) were recently reported, respectively, the safety analysis of wheat flour was not fully illustrated. Therefore, this review first summarizes the basic knowledge of NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of NIR spectroscopy in the quality and safety evaluation of tea products ( Lin and Sun, 2020 ), grain ( Caporaso et al, 2018 ), fruits and vegetables ( Nicolai et al, 2007 ), oilseeds and edible oils ( Li et al, 2020 ) have been reviewed. Although reviews on wheat-based products ( Badaró et al, 2022 ) and wheat flour ( Du et al, 2022 ) were recently reported, respectively, the safety analysis of wheat flour was not fully illustrated. Therefore, this review first summarizes the basic knowledge of NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…9 In this study, a much larger data set was collected from the latest publications, and feature selection with nonlinear regression modeling approaches was employed to link the data set and antioxidant activity, which all contributed to the better performance in test data sets. 4,8,16,37,38 3.3. Prediction of Dipeptides with Potentially High Antioxidant Activity from the Models.…”
Section: Resultsmentioning
confidence: 99%
“…Technically, R 2 CV could not describe the model’s performance in an unknown data set because the data used to obtain R 2 CV were used in model building . In this study, a much larger data set was collected from the latest publications, and feature selection with nonlinear regression modeling approaches was employed to link the data set and antioxidant activity, which all contributed to the better performance in test data sets. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…Spectral modeling techniques such as ultraviolet−visible (UV− vis) or near-infrared (NIR) spectra play an increasingly important role in the analysis of physical and chemical properties in agriculture, 1 industry, 2 environmental monitoring, 3 and food. 4 Generally, any materials or productions with different kinds of quantitative and qualitative components will generate specific spectral data, which contributes to the principle of composition measurement. However, just obtaining spectral data is still far from the mark of accurately predicting component composition because the original spectra signals inevitably involve serious background matrix effect due to sensor hardware design and measurement environment influence.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral modeling techniques such as ultraviolet–visible (UV–vis) or near-infrared (NIR) spectra play an increasingly important role in the analysis of physical and chemical properties in agriculture, industry, environmental monitoring, and food . Generally, any materials or productions with different kinds of quantitative and qualitative components will generate specific spectral data, which contributes to the principle of composition measurement.…”
Section: Introductionmentioning
confidence: 99%